The role of VWF/FVIII in thrombosis and cancer progression in multiple myeloma and other hematological malignancies. (23rd June 2022) - Comerford, Claire; Glavey, Siobhan; Quinn, John; O'Sullivan, Jamie M.
Abstract: Cancer associated thrombosis (CAT) is associated with significant morbidity and mortality, highlighting an unmet clinical need to improve understanding of the pathophysiology of CAT. Multiple myeloma (MM) is associated with one of the highest rates of thrombosis despite widespread use of thromboprophylactic agents. The pathophysiology of thrombosis in MM is multifactorial and patients with MM appear to display a hypercoagulable phenotype with potential contributory factors including raised von Willebrand factor (VWF) levels, activated protein C resistance, impaired fibrinolysis, and abnormal thrombin generation. In addition, the toxic effect of anti‐myeloma therapies on the endothelium and contribution to thrombosis has been widely described. Elevated VWF/factor VIII (FVIII) plasma levels have been reported in heterogeneous cohorts of patients with MM and other hematological malignancies. In specific studies, high plasma VWF levels have been shown to associate with VTE risk and reduced overall survival. While the mechanisms underpinning this remain unclear, dysregulation of the VWF and A Disintegrin And Metalloprotease Thrombospondin type 1, motif 13 (ADAMTS‐13) axis is evident in certain solid organ malignancies and correlates with advanced disease and thrombosis. Furthermore, thrombotic microangiopathic conditions arising from deficiencies in ADAMTS‐13 and thus an accumulation of prothrombotic VWF multimers have been reported in patients with MM, particularly in association with specific myeloma therapies. This review will discuss current evidence on the pathophysiological mechanisms underpinning thrombosis in MM and in particular summarize the role of VWF/FVIII in hematological malignancies with a focus on thrombotic risk and emerging evidence for contribution to disease progression.